1999
DOI: 10.1007/bf02494822
|View full text |Cite
|
Sign up to set email alerts
|

Optically active (2-aminomethylferrocenyl) phosphines with the phosphorus chiral center

Abstract: The reaction of an enantiomeric planar-chiral palladium derivative of dimethylaminomethylferrocene with PhMePLi in THF at room temperature afforded a t.5 : 1.0 mixture of diastereomeric aminophosphines containing the phosphorus asymmetrical center along with a chiral plane. The absolute configuration of the phosphorus atom was determined based on the X-ray diffraction data for the complex of the minor diastereomer with Pdl~. The presence of the (S)-chiral plane in the initial palladium compound favors the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Our group has been interested in reactions of CPCs with alkali metal phosphides because of possible transformations of cyclopalladated complexes into aminophosphines, diphosphines and related compounds containing a PR 2 group and another functionality. Previously, brief studies by Sokolov et al [3,4], Bolm et al [5] and Dunina et al [6] revealed that PPh 3 adducts of C,N-cyclopalladated complexes react with LiPPh 2 or KPPh 2 to yield either the corresponding aminophosphines or their Pd(0) complexes. Recently, we reported a detailed investigation of the LiPPh 2 reactions with the dinuclear chloro-bridged CPC 1 and showed that three products are formed in these transformations: (1) the corresponding mononuclear derivative 2 with Ph 2 P(CH 2 ) 4 OH as an auxiliary ligand, (2) complex 3, which is the m-Cl-m-PPh 2 analog of dimer 1, and (3) ortho-(diphenylphosphino)benzylamine 4 (Scheme 1) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our group has been interested in reactions of CPCs with alkali metal phosphides because of possible transformations of cyclopalladated complexes into aminophosphines, diphosphines and related compounds containing a PR 2 group and another functionality. Previously, brief studies by Sokolov et al [3,4], Bolm et al [5] and Dunina et al [6] revealed that PPh 3 adducts of C,N-cyclopalladated complexes react with LiPPh 2 or KPPh 2 to yield either the corresponding aminophosphines or their Pd(0) complexes. Recently, we reported a detailed investigation of the LiPPh 2 reactions with the dinuclear chloro-bridged CPC 1 and showed that three products are formed in these transformations: (1) the corresponding mononuclear derivative 2 with Ph 2 P(CH 2 ) 4 OH as an auxiliary ligand, (2) complex 3, which is the m-Cl-m-PPh 2 analog of dimer 1, and (3) ortho-(diphenylphosphino)benzylamine 4 (Scheme 1) [7].…”
Section: Introductionmentioning
confidence: 99%
“…Later, the same group published results obtained for the reaction of (S pl ,S pl )-91 with the prochiral lithium phosphide, LiPMePh (Scheme 31) [67]. Two diastereomers of aminophosphine 92 were obtained in 52% total yield and were separated using column chromatography on silica gel.…”
Section: Reactions Of Cyclopalladated Complexes With Metal Phosphidesmentioning
confidence: 99%
“…Activation of C–H bonds of substituted ferrocenes in the presence of stoichiometric or catalytic amounts of transition metals, e.g., palladium, ruthenium, or iridium, has been used for the synthesis of planar-chiral ferrocenes . Functionalized ferrocenes have been obtained by treatment with alkynes, alkenes, arenes, arylboronic acids, carbon monoxide, and phosphides . Gu, You, and co-workers, for example, converted ferrocene 53 into planar-chiral 1,2-disubstituted 268 in up to 99% ee by means of a palladium-catalyzed direct arylation with arylboronic acids (Scheme ) …”
Section: Miscellaneous Syntheses Of 12-disubstituted Ferrocenesmentioning
confidence: 99%